Biotransformation Of Ferulic Acid Extracted From Biomass To Biovanillin By Amycolatopsis Sp. Atcc 39116 - Abu Sepian, Noor Raihana (2014)
This study focuses on the biotransformation of synthetic and extracted ferulic acid (FA) from lignocellulosic biomass using growing cells of Amyco/alopsis sp. ATCC 39116 as a biocatalyst. Preliminary alkaline hydrolysis showed that the hydrolyzate from oil palm empty fruit bunch (OPEFB) contained the highest amount of FA (199.4 mg/l) among the other three lignocellulosic wastes (i.e. oil palm frond, coconut fiber and sheIl). Optimization of extraction was carried out using Response Surface Methodology (RSM) via Central Composite Design (CCD) on the effect of three independent variables, i.e. concentration of NaOH (1.5-5 M), solid/liquid ratio (0.03-0.084 g/ml) and time (16-32 h). The optimum FA concentration of 2.04 mg/g OPEFB (365.19 mg/l) was obtained under the optimal conditions of 1.5 M ofNaOH concentration, 0.03 g/ml of solid/liquid ratio and 32 h of extraction time. The extracted FA was further purified using polyvinylpolypyrrolidone (PVPP) and activated carbon, and about 97.26% was successfully recovered from the extract using PVPP. The partially purified FA was converted into 38.47% molar yield of vanillin, showing the ability of Amyco/alopsis sp. ATCC 39116 to convert the extracted FA from lignocellulosic waste.